A Rare Case of Tuberculosis with Sacrococcygeal Involvement Miming a Neoplasm - Walid Osman; Meriem Braiki; Zeineb Alaya; Thabet Mouelhi; Nader Nawar; Mohamed Ben Ayeche (Case Reports in Orthopedics)
Infection of the lumbosacral junction by tuberculosis is quite rare and occurs in only 1 to 2% of all cases of spinal tuberculosis; moreover, isolated sacrococcygeal or coccygeal tuberculosis is much rarer. Failure to identify and treat these areas of involvement at an early stage may lead to serious complications such as vertebral collapse, spinal compression, and spinal deformity. In the present paper, we report an uncommon case of spinal tuberculosis with sacrococcygeal location revealed by a chronic low back pain that was successfully managed. Computed tomography scan and magnetic resonance imaging of the pelvis revealed a lytic lesion affecting both of sacrum and coccyx causing osseous destruction and suggesting a malignant process. A surgical biopsy was performed to establish the tissue diagnosis. Histopathological report confirmed the diagnosis of skeletal tuberculosis. The patient was treated with antibacillary chemotherapy for a period of 9 months. The follow-up period was of 36 months. There was a full recovery and the patient was asymptomatic.